2014
DOI: 10.1016/j.apsusc.2014.07.194
|View full text |Cite
|
Sign up to set email alerts
|

Modification of acid sites in ZSM-5 by ion-exchange: An in-situ FTIR study

Abstract: A study of the acid sites in M n+ -ZSM-5 zeolites (M n+ = H + , Al 3+ , Ca 2+ , and Ba 2+ ), synthesized by ion-exchange from the NH 4 + form, has been carried out using X-ray diffraction, 27 Al MAS NMR, and in-situ FTIR spectroscopy. X-ray diffraction data indicate that the crystalline structure of ZSM-5 is maintained on ion-exchange. 27 Al MAS NMR spectroscopy confirms that Lewis acid sites in all of the M n+ -ZSM-5 zeolites are mainly located on the tetrahedral aluminum atoms in the zeolite framework. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 70 publications
2
39
0
Order By: Relevance
“…Accordingly, most of the research was focused on finding the ways to suppress coke formation. The different approaches has been applied such as using different zeolite frameworks [8,9], or catalyst modification [10,11], or addition of co-reactant [12,13] or increasing the reaction pressure [14], modification of the reaction conditions [15], and addition of promoters.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, most of the research was focused on finding the ways to suppress coke formation. The different approaches has been applied such as using different zeolite frameworks [8,9], or catalyst modification [10,11], or addition of co-reactant [12,13] or increasing the reaction pressure [14], modification of the reaction conditions [15], and addition of promoters.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a high catalyst concentration led to a high Ni content in ZSM-5and an increase in number of active sites of catalysts. After the active site increases, the gasoline yield increases [1,6,26].…”
Section: Resultsmentioning
confidence: 99%
“…Cracking has been accomplished with solid catalysts, such as H-ZSM-5, metal-impregnated MCM-41, and Y zeolite, which have good selectivity and appropriate pore size. Metal catalysts also support solid carriers, such as silica, alumina, carbon, zeolite, and zeotype structures [6,[14][15][16][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, aluminosilicate zeolites, such as ZSM-5, beta and Y, are considered as supports in the HDS process due to their high hydrothermal stability, favourable isomerization properties and particularly abundant B acid sites. [5][6][7] Wu and co-workers prepared a series of metal cationfunctionalized M + -ZSM-5 (M + ¼ H + , Al 3+ , Ca 2+ and Ba 2+ ) materials and the characterization results showed that H + -ZSM-5 possessed the most accessible acid sites. 6 The B acids were derived from the bridge hydroxyl groups, which connected with Al and Si atoms, and the varying ratios of B acids to L acids coincided well with the different amounts and types of metal cations.…”
Section: Introductionmentioning
confidence: 99%